Barriers to care linkage and educational impact on unnecessary MASLD referrals - Lee, Jun-Hyuk; Yoon, Eileen Laurel; Oh, Ju Hyun; Kim, Kyunam; Ahn, Sang Bong; Jun, Dae Won (Frontiers in Medicine, 2024)
Background The importance of primary care physicians (PCPs) in managing metabolic dysfunction-associated steatotic liver disease (MASLD) has increased. This study aimed to assess the effectiveness of an online educational program on MASLD among physicians. Methods In total, 869 physicians (72 physicians at referral centers and 797 PCPs) participated in this study. They completed an initial survey regarding their clinical practices for patients with MASLD, followed by a second online survey 8 weeks after receiving a series of seven weekly sets of educational materials on MASLD. Results In the baseline survey, most PCPs did not routinely evaluate the stage of hepatic fibrosis in MASLD; they typically initiated assessments based on elevated liver enzyme levels. Only a limited number of PCPs used vibration-controlled transient elastography. The main hurdles in managing MASLD were “the absence of a fee for patient education” for PCPs and “short consultation time” for referral-center physicians. In the follow-up survey, the percentage of liver fibrosis assessments using noninvasive tests increased from 7.0 to 11.2%. Additionally, evaluations for cardiovascular disease increased from 3.9 to 8.2%, and the risk of ischemic stroke increased from 13.7 to 16.9%. The percentage of immediate referrals of patients to specialists after an MASLD diagnosis decreased from 15.4 to 12.3%. Conclusion The discrepancies in management strategies and viewpoints regarding MASLD between PCPs and referral-center physicians can hinder efforts to mitigate the disease burden. Increasing awareness among PCPs regarding MASLD through a 7-week education program led to a reduction in unnecessary referral rates and an increase in cardiovascular evaluations.